Mia and the Too Big Tutu - Farley, Robin; Ivanov, A. (Aleksey); Ivanov, O. (Olga) (New York : HarperCollins, 2010)
Mia the kitten is so excited about her first day of ballet class that she accidentally brings her big sister's tutu instead of her own.
003-005.
Keywords: Ballet dancers -- Fiction; Cats -- Fiction; Animals -- Fiction